Concepts by Koneczny and Giertych and their Contribution to the Durability of National Mythology - Nikodem Jakubowski, Marek (Practica et Speculativa: Studies Offered to Professor Andrzej M. Kaniowski, 2022)
This paper does not aim to present an outline of Feliks Koneczny’s (undoubtly interesting) theory of civilizations but rather tries to show the dangers of an attempt to update it while ignoring the historical context in which it arose. This attempt to popularize Koneczny’s thought throughout the world must have proved counterproductive.